2010
DOI: 10.4103/0019-5154.60369
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations in human immunodeficiency virus infected patients

Abstract: Background:Oral lesions are common among Human Immuno deficiency Virus (HIV)-positive patients. The pattern of oral features in these persons may differ in separate settings.Aims:To find out the spectrum of oral manifestations among a section of seropositive individuals attending the antiretroviral therapy (ART) centre of a referral hospital.Materials and Methods:A total of three hundred and twenty-one newly diagnosed seropositive patients were enrolled in this study. Of these, ninety-four patients who demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
2
17
1
Order By: Relevance
“…9,10 Here productive age group (31 to 41) is the predominant affected group (50%). Even though heterosexual route (71%) is the commonest mode of transmission in our study, most of our patients are males (65%) in contrast to a study by Sen et al 11 The commonest oral lesion noted in our study is oral candidiasis (50%) as in a study by Lamster et al 12 Erythematous candidiasis is more frequently noted in the immune suppressed group whose CD4 count <200. Thus it has got prognostic value as suggested by Kerdpon et al 13,14 In contrast to oral herpes, oral hairy leucoplakia (7.7%) is noted only in immune suppressed status.…”
Section: Discussioncontrasting
confidence: 75%
“…9,10 Here productive age group (31 to 41) is the predominant affected group (50%). Even though heterosexual route (71%) is the commonest mode of transmission in our study, most of our patients are males (65%) in contrast to a study by Sen et al 11 The commonest oral lesion noted in our study is oral candidiasis (50%) as in a study by Lamster et al 12 Erythematous candidiasis is more frequently noted in the immune suppressed group whose CD4 count <200. Thus it has got prognostic value as suggested by Kerdpon et al 13,14 In contrast to oral herpes, oral hairy leucoplakia (7.7%) is noted only in immune suppressed status.…”
Section: Discussioncontrasting
confidence: 75%
“…Folliculitis was the most common manifestations (6.6%). This was comparable with the study by Sud et al and Srikant KP et al, 8% of folliculitis lesions were reported [9,10]. The mean CD4 count in bacterial infection was 220.2 cells/cu mm, this was reported to be 245.33 cells/cu mm by Jing et al [11].…”
Section: Discussionsupporting
confidence: 87%
“…OHL is a benign lesion of the oral mucosa related to infection by Epstein-Barr virus (EBV). It is generally observed in immunocompromised patients, in particular HIV-positive individuals [3], and may be an early sign of HIV infection when the patient’s serological status has not yet been identified [2,4]. The recognition of early signs of immune suppression may have a significant impact on the treatment decisions for HIV infection as well as on patients’ survival and their quality of life [4].…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, oral lesions are the first sign of HIV infection [2]. Oral hairy leukoplakia (OHL) is one of the oral lesions strongly associated with HIV infection [2]. OHL is a benign lesion of the oral mucosa related to infection by Epstein-Barr virus (EBV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation